The UK's Privatisation Experiment: The Passage of Time Permits a Sober Assessment - David Parker (Center for Economic Studies and ifo Institute (CESifo), 2004)
This chapter looks at the UK's privatisation experiment, which began from the late 1970s. It considers the background to the UK's privatisations, which industries were privatised and how, and summarises the results of studies of performance changes in privatised companies in the UK. It looks at the relative roles of competition, regulation and ownership changes in determining performance improvement. It concludes by looking at the wider lessons that might be learned from the UK's privatisation experiment, including the importance of developing competitive markets and, in their absence, effective regulatory regimes.
Keywords: 330; UK; privatisation; competition regulation; privatisation lessons